The Future Architecture of Samarkand (Journal of Architectural Design, 2023)
This article reflects that the artistic expressiveness of architectural forms and images should be in the first place in the architecture of the future of Samarkand, and they should attract the attention of the viewer with their unusual appearance and architectural and engineering solutions